The expert system of genotype discrimination for D5S818 locus based on near-infrared spectroscopyâprincipal discriminant variate - Zai-Zhen Wu; Jian-Hua Tang; Bin Zhang; Li-Ping Guo; Hong-Ping Xie; Bing-Ren Gu (Elsevier, 2012)
This paper studied the expert system of genotype discrimination for the STR locus D5S818 based on near-infrared spectroscopyâprincipal discriminant variate (PDV). Six genotypes, i.e. genotypes 10â10, 10â11, 11â11, 11â12, 11â13 and 13â13, were selected as research subjects. Based on the optimum polymerase chain reaction (PCR) conditions, about 54 measuring samples for each genotype were obtained; these samples were tested by near-infrared spectroscopy directly. With differences between homozygote genotypes and heterozygote ones, and differences of the total number of core repeat units between the six genotypes, two types of genotyping-tree structure were constructed and their respective PDV models were studied using the near-infrared spectra of the samples as recognition variables. Finally, based on the classification ability of these two genotyping-tree structures, an optimum expert system of genotype discrimination was built using the PDV models. The result demonstrated that the built expert system had good discriminability and robustness; without any preprocessing for PCR products, the six genotypes studied could be discriminated rapidly and correctly. It provided a methodological support for establishing an expert system of genotype discrimination for all genotypes of locus D5S818 and other STR loci. Keywords: Short tandem repeat, Near-infrared spectroscopy, Principal discriminant variate, Genotyping-tree structure, Expert system